The Associations of Serum Folate Forms with Metabolic Dysfunction-Associated Fatty Liver Disease and Liver Fibrosis: A Nationwide Cross-Sectional Study - Hai Zhao; Wei Fan; Yan Yan; Yuxing Liu; Xuejun Kang (Metabolites, 2025)
Background: Accumulating evidence indicates a link between folate and metabolic dysfunction-associated fatty liver disease (MAFLD). Objectives: The aim of this study was to ascertain whether different serum folate forms are associated with newly defined MAFLD as well as liver fibrosis in the US general population. Methods: This cross-sectional study used data from the 2017–2020 (March) cycle and 2017–2018 cycle of the National Health and Nutrition Examination Survey (NHANES) in the US. Hepatic steatosis and fibrosis were evaluated by transient elastography, which employed controlled attenuation parameters and liver stiffness measurements as assessment indicators. Results: 7447 eligible individuals were included. The estimated prevalence of MAFLD and liver fibrosis was 51.6% (95% confidence interval [CI]: 50.4–52.7%) and 10.0% (95% CI: 9.3–10.7%). After adjusting for confounding factors, for every 1 nmol/L increase in serum 5-methyltetrahydrofolate (5-mTHF), the risk of developing liver fibrosis decreased by 1% (95% CI: 1–2%, p < 0.001), and the risk of developing MAFLD decreased by 1% (95% CI: 0–2%, p = 0.005). There were also significant differences in indicators such as alanine aminotransferase (ALT), gamma-glutamyl transaminase (GGT), and C-reactive protein (CRP) between the MAFLD group and the non-MAFLD group (all p values < 0.001). Conclusions: This study suggests the prevalence of MAFLD and liver fibrosis decreased significantly with the increase in serum 5-mTHF concentration.